The occurrence of C-shaped root canal in Malaysian population (Bangladesh Journal of Medical Science, 2013)
Background: The recognition of unusual canals configurations and variations are essential for successful endodontic diagnosis and treatment. This study was aimed to investigate the occurrence of C- shaped root canal in Malaysian population. Design: This is an in vitro study whereby 241 extracted human first and second molars with intact root were collected from several dental clinics in Malaysia. Materials and Methods: The roots were sectioned at three levels: subpulpal level, 3mm from apical tip and middle level between the first and last level. The appearance of the root canal sections were assessed using stereomicroscope (Leica, Germany) and pictures were taken. Data were analyzed statistically using Fishers Exact and Binomial test with p